Áfido del algodón Aphis gossypii / Áfido del algodón, ciclo de vida - Hugh A. Smith; Nicole Casuso; Lorena Lopez (EDIS)
The cotton or melon aphid is a serious pest of many horticultural crops in Florida. This Spanish language fact sheet aids in its identification.